A comparisison of some numerical methods for computing the inverse kinematics of redundant parallel robots - Lương, Tuấn Anh; Nguyễn, Khang Văn (Journal of Computer Science and Cybernetics, 2013)
This paper presents a comparison of three numerical methods for computing the inverse kinematics of redundant parallel robots: the improved Newton-Raphson method, the coordinate and velocity projection method and the method using the ‘fsolve’ command in Matlab. The results obtained by these methods for computing the inverse kinematic problem of the planar redundant parallel robot 3RRRP show that the improved Newton-Raphson method has advantages of high accuracy and calculating faster time over the others.